Clinical and Etiological Structure of Nosocomial Infections in Bulgaria for the Period 2011-2016 - Mitova Y. (Sciendo, 2017)
Despite their partial diagnosis and registration, nosocomial infections are widespread in Bulgaria and they are of great healthcare, social and economic importance for the society. Statistical processing of official information for the period 2011-2016 shows that the incidence of registered NI among hospitalized patients in Bulgaria is below 1%. In the clinical structure of NI in the above mentioned period, the infections of the surgical site are leading with a prevailing share of 20.67%. S. aureus (19.74%) and E. coli (19.33%) have the highest incidence in the etiological deciphering of infections of the surgical site. Leading etiological agents of lower respiratory tract infections (including pneumonia) in Bulgaria are Acinetobacter spp. (24.12%) and Pseudomonas spp. (20.18%). Urinary tract infections have a relative share of 15.08% in the clinical structure of NI. They are primarily caused by E. coli (28.95%). In bloodstream infection, coagulase-negative staphylococci (S. epidermidis prevailing) are isolated in 30.58% of the cases.